Mechanism of action and resistance to daptomycin in Staphylococcus aureus and enterococci (2016)
Lipopeptides are natural product antibiotics that consist of a peptide core with a lipid tail with a diverse array of target organisms and mechanisms of action. Daptomycin (DAP) is an example of these compounds with specific activity against Gram-positive organisms. DAP has become increasingly important to combat infections caused by Gram-positive bacteria because of the presence of multidrug resistance in these organisms, particularly in methicillin- resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococci (VRE). However, emergence of resistance to DAP during therapy is a well-described phenomenon that threatens the clinical use of this antibiotic, limiting further the therapeutic options against both MRSA and VRE. Thiswork will review the historical aspects of the development of DAP, as well as the current knowledge on its mechanism of action and pathways to resistance in a clinically relevant context.